Application of Discovery Learning Model with Peer Tutor Method to Improve Physics Learning Outcomes - Humairah, Nur Isna; Arafah, Kaharuddin; Hasniwati, Hasniwati (Indonesian Journal of Pedagogical and Social Sciences, 2024)
Abstract. This study aims to improve the physics learning outcomes of students through the application of discovery learning model with peer tutor method. The type of research is Classroom Action Research (CAR) with Kurt Lewin model design. The research subjects were X IPA 1 class at UPT SMAN 4 Gowa in the 2023/2024 school year. Data collection techniques used written tests. Data analysis techniques used quantitative and qualitative descriptive analysis. The results showed an increase in physics learning outcomes. The average value of physics learning outcomes before the action was 61,54 with a percentage of completeness of 23,33% in the very less category. The average value of physics learning outcomes in cycle I was 74,55 with a percentage of completeness of 54,17% in the less category. The average value of physics learning outcomes in cycle II was 75,71 with a percentage of completeness of 65,52% in the sufficient category. Thus, the discovery learning model with a peer tutor approach can improve physics learning outcomes in class X IPA 1 at UPT SMAN 4 Gowa. Keywords: learning outcomes, discovery learning, peer tutoring